2019
DOI: 10.2147/dddt.s166092
|View full text |Cite
|
Sign up to set email alerts
|

<p>Update in treatment of uveitic macular edema</p>

Abstract: Macular edema (ME) represents the most common cause for visual loss among uveitis patients. The management of uveitic macular edema (UME) may be challenging, due to its often recalcitrant nature. Corticosteroids remain the mainstay of treatment, through their capability of effectively controlling inflammation and the associated ME. Topical steroids may be effective in milder cases of UME, particularly in edema associated with anterior uveitis. Posterior sub-Tenon and orbital floor steroids, as well as intravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 155 publications
0
51
0
3
Order By: Relevance
“…In refractory DME cases, the part of vitrectomy without taking into consideration the tractional component is more disputable. Though studies have indicated that peeling of ILM could facilitate getting better results, others studies have depicted similar results by vitrectomy 15 .…”
Section: Resultsmentioning
confidence: 97%
“…In refractory DME cases, the part of vitrectomy without taking into consideration the tractional component is more disputable. Though studies have indicated that peeling of ILM could facilitate getting better results, others studies have depicted similar results by vitrectomy 15 .…”
Section: Resultsmentioning
confidence: 97%
“…To date, published reviews, articles and collected literature data about the approved use of Dex implant confirm its efficacy [4][5][6]. Nevertheless, in recent years several additional studies further confirmed the potential benefits of intravitreal Dex for various ocular pathologies with inflammatory etiopathogenesis and ME ( Figure 1).…”
Section: Introductionmentioning
confidence: 86%
“…The treatment of NIUs and associated ME is still very challenging. Since inflammation is the main pathogenic event in these disorders, corticosteroids, either systemic or regional, represent the mainstay of treatment [5]. Although effective, the use of systemic corticosteroids is limited due to numerous adverse effects [41].…”
Section: Pathogenesis Of Posterior Non-infectious Uveitismentioning
confidence: 99%
“…In einer Studie von Leder et al führte eine einmalige periokuläre Injektion von 20-40 mg Triamcinolon-Acetonid nach 1 Monat bei 53 % der Augen zu einer Rückbildung des Makulaödems [24]. Allerdings kommt es nach periokulärer Kortikosteroidgabe häufig zu Rezidiven mit der Notwendigkeit regelmäßiger Re-Injektionen [25].…”
Section: Kortikosteroideunclassified